Sustainable Development Planning in Kosovo - Francesco Citarella (European Regional Science Association (ERSA), 2006)
After eighteen months of intense preparation and work, in April 2003 the signing of MEMORANDUM OF COOPERATIVE RESEARCH between the NORTH ATLANTIC TREATY ORGANIZATION'S REGIONAL HEADQUARTERS ALLIED FORCES SOUTHERN EUROPE (AFSOUTH) and the DEPARTMENT FOR STUDIES ON THE ENVIRONMENT AND TERRITORY (DISAT) of the UNIVERSITY OF SALERNO was finalised. Within the framework of cooperation set up between NATO (AFSOUTH – NAPOLI) and DiSAT, we have been invited to carry out activities of study and research regarding the complex social, economic and security problems in Kosovo. Therefore, with the aim of contributing to the consolidation of the process of peace and development in Kosovo, interdisciplinary research has been carried out in the Region last September, preliminary to the drawing up of a REPORT ON SUSTAINABLE DEVELOPMENT PLANNING IN KOSOVO. The concept of security, traditionally seen from a purely military perspective, has gradually grown to embrace economic aspects, political-cultural aspects as well as others of a different nature. To guarantee security, then, means not so much or at least, not only, to increase the weight of traditional power factors but rather to reduce to a minimum the conditions of specific vulnerability. Functional to this aim would be to achieve an accurate analysis in order to consent the recommending of such actions that could avoid the most critical and dangerous union of forces. A return to the study then of the problems that encourage these phenomena, their dimension and collocation in space appears to be the longest and most laborious way but also the only one possible. An analysis of the present day economic and political questions in the region must not neglect, furthermore, the considerable imbalances existing in the region between population and uses of the resources. Infact, the report, after having indicated the principal lines of development, follows with the formulation of projects well inserted into a strategic framework, so as to overcome the gap existing between plans, programmes, laws and recommendations on the one hand and real capacity and determination to succeed on the other.
Keywords: 330